Problems Focused Coping Penderita HIV Positif - Priharwanti, Ardiana; Budi Raharjo, Bambang (Universitas Negeri Semarang, 2017)
HIV / AIDS merupakan masalah besar dan baru-baru ini menarik untuk diangkat sebagai penelitian psikososial, terutama pada subyek yang beresiko tinggi. Ã‚Â Sejumlah kasus sindrom kejiwaan telah diidentifikasi dalam kaitannya dengan infeksi HIV Penderita HIV cenderung menggunakan mekanisme koping yang maladaptive dalam menyelesaikan masalah yang dihadapinya. Penelitian ini merupakan penelitian kualitatif di Kabupaten Batang yang difokuskan pada problems focused coping penderita HIV Positif. Informan awal ditentukan dengan teknik purposive sampling, selanjutnya ditentukan dengan teknik snowball sampling. Metode pegumpulan data diperoleh melalui wawancara mendalam (indepth interview) terhadap 5 informan utama penderita HIV positif, teman sebaya, keluarga penderita dan 3 informan triangulasi yang terdiri dari KPA Batang, Manajerkasus FKPB, dan pendamping HIV positif.Selain permasalahan menurunnya kesehatan fisik sebagai stressor pertama, penderita HIV Positif dihadapkan pada permasalahan stigma di masyarakat yang cenderung menyebabkan penderita melakukan koping strategi salah satunya adalah problems focused coping.HIV / AIDS is a big problem and recently has become an interesting topic for psycho-social study, especially for high-risk subjects. A number of psychiatric syndromes cases have been identified in relation to HIV infection. The complexity of the problems faced by people with HIV can lead to the lower quality of life. People with HIV tend to use maladaptive coping strategies to solve their problems.This study is a qualitative study in Batang District with a focus on problems focused coping of people with HIV. Initial informant was determined using purposive sampling, then further informants were determined using snowball sampling technique. The data were collected using an in-depth interview to 5 key informants (people with HIV), peers, family and three triangulation informants consisting of AIDS Control Commission of Batang, FKPB case manager, and HIV patient companion. In addition to a decline in physical health problems as the main stressor, HIV people are faced with the problems of a stigma that causes them to form coping strategiesone of which is focused coping problems.